Words of fire : independent journalists who challenge dictators, druglords, and other enemies of a free press - Collings, Anthony (New York University Press, 2001)
If journalism is the first draft of history, then independent journalists are surely its most daring composers. Along such celebrated and high-profile figures as Christiane Amanpour and Wolf Blitzer, there exists a stratum of journalists self-employed, working under dire conditions, and with minimal resources who often place themselves at ground zero of world events. In this gripping account, Anthony Collings takes us into the world of independent journalists, and the daily challenges they face confronting dictators, hostile military, and narcoterrorists. Unfettered by any ties to those in positions of power, these guerrilla journalists are often the first on a story whether reporting on corruption in Mexico, organized crime in Russia, or sexual scandal in the Middle East and accordingly face the brunt of their subject's wrath. Collings, who has himself been held captive while on assignment, here focuses less on those nations in which the press is either largely free (such as the U.S. or Western European democracies) or aggressively restricted (as in China), and more on those "battleground countries" where the eventual outcome of the struggle between state and fourth estate remains unclear. Relying on interviews, professional contacts, and his own experiences, Collings explores the dilemmas and strategies of journalists who persevere in the face of war, repressive governments, and criminal aggression, with particular emphasis on the role of the Internet. At a time when journalism is increasingly a profession under siege, Words of Fire forces into the spotlight a more positive side of the profession, those who pursue journalism not for profit or fame but as a personal crusade